Alterations of gut microbiota and short-chain fatty acids induced by Balantidium polyvacuolum in the hindgut of Xenocyprinae fishes providing new insights into the relationship among protozoa, gut microbiota and host - Bu, Xialian; Li, Zhongyang; Zhao, Weishan; Zeng, Qingwen; Chen, Yushun; Li, Wenxiang; Zou, Hong; Li, Ming; Wang, Guitang (Frontiers in Microbiology, 2023)
Parasitic ciliates are protozoans with a global distribution. Along with the gut microbiota, they have formed a micro-ecosystem that affects the host's nutrition, metabolism, and immunity. The interactions and relationships among the three components of this microecosystem (protozoa, gut microbiota, and host) remain only partially understood. Xenocypris fish and the unique ciliate Balantidium polyvacuolum in its hindgut are good materials to study the interplay. By 16S rRNA gene amplicon sequencing and short-chain fatty acids (SCFAs) identification, we found that the gut microbiota of B. polyvacuolum-infected X. davidi and X. argentea had higher diversity, richness, and evenness than uninfected ones. B. polyvacuolum could lead to an increase of Fusobacterium and Chloroflexi in both X. davidi and X. argentea, while significantly increase the abundance of genera Romboutsia and Clostridium in X. argentea. Besides, B. polyvacuolum could significantly increase the content of total SCFAs and acetic acid in X. davidi and increase the concentrations of propionic, isobutyric and butanoic acids in X. argentea. Furthermore, correlation analyses showed that B. polyvacuolum may alter SCFAs by affecting key SCFAs-producing bacteria such as Clostridium and Cetobacterium. This study greatly expands our understanding of relationships among B. polyvacuolum, gut microbiota and host Xenocypris fish, which sheds new insights into the mechanism of interaction among protozoa, gut microbiota and host.